Work-Based Networked Learning: A bottom-up approach to stimulate the professional development of teachers - Schreurs, Bieke; De Laat, Maarten (Proceedings of the International Conference on Networked Learning, 2012)
Networked learning is an important driver for informal professional development and workplace learning based on social relationships. However powerful networked learning may be, there is a problem when it comes to making it a real asset within organizations. This may seem as a paradox, but networked learning activities are mostly invisible to others, sometimes the learners themselves might not even be aware of the learning that occurs. As a consequence networked learning in organizations goes undetected, remains off the radar of HR departments and is therefore hard to asses, manage and value (Wenger, Trayner, & De Laat, 2011). Bearing this in mind we acknowledge a great need for empirical research and tools that can raise awareness about networked learning activities to make it visible, amplify the benefits of it and strengthen the social relations through which it occurs. Through our research practice we have experimented with several visualization methods of informal learning networks (De Laat, 2011; Haythornthwaite & De Laat, 2012) and developed a research methodology around this practice, We will present the results of a descriptive study conducted with 22 teachers in a secondary school in the Netherlands alongside the design guidelines for a research practice to visualize (personal) professional development networks driven by networked learning issues. The goal of this paper is to increase our understanding of how we can make networked learning activities visible and as a consequence help organisations to support a bottom-up approach to stimulate professional development amongst teachers.